2017
DOI: 10.1186/s13018-017-0511-5
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive percutaneous osteosynthesis versus ORIF for Sanders type II and III calcaneal fractures: a prospective, randomized intervention trial

Abstract: BackgroundThis randomized controlled trial compared the clinical outcomes and complications of a novel minimally invasive percutaneous osteosynthesis (MIPO) with those of conventional treatment via an extended L-shaped lateral approach for calcaneal fractures.MethodsSixty-four patients with displaced intraarticular calcaneal fractures were enrolled. The patients were randomly allocated to receive either MIPO (29 patients) or open reduction and internal fixation via an extended L-shaped lateral approach (35 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 26 publications
(38 reference statements)
2
36
0
2
Order By: Relevance
“…Currently, open reduction and internal fixation (ORIF) is considered the reference standard treatment of displaced intraarticular fractures of the calcaneus (9,10), because anatomic reduction is important for feet and ankles to have functional outcomes. Also, ORIF is the best method for achieving calcaneal morphology restoration and anatomic reduction of the articular surface (11,12).…”
mentioning
confidence: 99%
“…Currently, open reduction and internal fixation (ORIF) is considered the reference standard treatment of displaced intraarticular fractures of the calcaneus (9,10), because anatomic reduction is important for feet and ankles to have functional outcomes. Also, ORIF is the best method for achieving calcaneal morphology restoration and anatomic reduction of the articular surface (11,12).…”
mentioning
confidence: 99%
“…Many studies have compared the extended lateral approach and minimally invasive techniques to minimize the wound complication rate. [22][23][24][25] Most commonly, the sinus tarsi approach was used because it provides a direct exposure of the posterior facet. Kline et al [22] reported an overall wound complication rate of 6% in patients treated using the minimally invasive sinus tarsi approach.…”
Section: Discussionmentioning
confidence: 99%
“…The primary concern with this approach is a high complication rate. [36][37][38][39][40][41][42][43] Some techniques can be employed to decrease the risk of complications related to this approach. For example, the corner of the incision should be curved to avoid significant wound complications.…”
Section: Conservative Treatment Vs Open Reduction and Internal Fixationmentioning
confidence: 99%
“…Wound complication rates have been reported to range from 0% to 15.4% with the sinus tarsi approach, 42,65 being lower than those reported for the extended lateral approach (range, 10% to 37.1%). 36,[41][42][43]67 Kline et al 48 performed a retrospective review to compare the outcomes of displaced intra-articular calcaneal fractures treated with ORIF via an extensile approach vs a minimally invasive sinus tarsi approach. Clinical results were similar for the 2 approaches, but the minimally invasive approach had a significantly lower incidence of wound complications and secondary surgeries.…”
Section: Internal Fixation Of Displaced Intraarticular Calcaneal Fracmentioning
confidence: 99%